Effects of Yoga in Daily Life program in rheumatoid arthritis: A randomized controlled trial - Silva Pukšić; Joško Mitrović; Melanie-Ivana Čulo; Marcela Živković; Biserka Orehovec; Dubravka Bobek; Jadranka Morović-Vergles (Elsevier, 2021)
Objectives: To explore the feasibility and effectiveness of a yoga program in improving health-related quality of life (HQOL), physical and psychological functioning in rheumatoid arthritis (RA) patients. Design: Single-centre parallel-arms randomized controlled trial comparing yoga (n = 30) and education control group (n = 27). Setting: Tertiary care University hospital. Intervention: A 12-week yoga program, based on the Yoga in Daily Life system, included 2x weekly/90-minute sessions. The control group had 1xweekly/60-minute educational lectures on arthritis-related topics. Main outcome measures: Assessments were performed at baseline, 12 (post-intervention) and 24 weeks (follow-up). The primary outcome was change in The Short Form-36 (SF-36) HQOL at 12 weeks. Linear regression analysis was adjusted for baseline scores. Results: No significant between-group differences were found for SF-36 (all p > 0.05). At 12 weeks the adjusted mean difference between groups favoured yoga for Functional Assessment of Chronic Illness Therapy-fatigue (5.08 CI 1.29 to 8.86; p = 0.009) and Hospital Anxiety and Depression Scale (HADS)-depression (−1.37 CI −2.38 to −0.36); p = 0.008) and at 24 weeks for HADS-anxiety (−1.79 CI −3.34 to − 0.23; p = 0.025), while the impact on fatigue was sustained (5.43 CI 1.33 to 9.54, p = 0.01). The program had no impact on RA disease activity. Feasibility outcomes included recruitment rate 16 %, retention 80.7 %, and adherence to yoga 87.5 vs 82.7 % for control. No serious adverse events were recorded. Conclusions: Yoga in Daily Life program was not associated with change in health-related quality of life of RA patients. Significant improvements in fatigue and mood were observed at postintervention and follow-up. This yoga program was found feasible and safe for patients and may complement standard RA treat-to-target strategy.